청소년의 스트레스, 사회적지지, 건강행위와의 관계 - 김영아; Kim Young-Ah (Adong Kanho Hakhoe chi, 2001)
The subjects were 349 high school boys and girls who were 10th and 11th graders in Seoul, Korea. Statistical analysis included percentages, means, Pearson correlation coefficient, ANOVA, t-test, and stepwise multiple regression analysis. As a result, there were positive correlations between social support, stress reduction and increases in health behavior. Stepwise multiple regression analysis of social support, stress, and adolescents health behavior showed that social support explained 26.3％ of the variance in health behavior, The more social support subjects experienced more health behavior level and the less the correlated stress level. In the area of demographic attributes, gender, height, weight, grade level, socioeconomic level of the parents, and stress were significantly correlated, grade levels, religion, socioeconomic level of parents and social support. sibling order, religion, socioeconomic level of the parents, parents education, occupation of father. and health behavior were statistically significant The findings indicated stress was a negative factor in health behavior, and social support was a positive factor in reducing stress and promoting health behavior. To reduce adolescents stress and to promote health behavior, we should endeavor to develop realistic social support programs.